ADAPTIVE TRACKING CONTROL FOR TWIN ROTOR MULTIPLE-INPUT MULTIPLE-OUTPUT BASED ON ISS STABILIZATION - Chi, Nguyen Van (Vietnam Journal of Science and Technology, 2016)
This paper proposes the angle tracking control method for Twin rotor multi-input multiple-output (TRMS) using the input-to-state stability theory (ISS) for nonlinear systems. To apply this theory, the model of TRMS is rewritten by an Euler-Lagrange forced model with uncertain parameters and input disturbances. The uncertain parameters are the potential energies depended on the mass of TRMS’parts and the input disturbances are considered the friction force, the flat cable force, the effects of the speed of the main rotor on the horizontal movement and the speed of tail rotor to the vertical movements. Using modificated model of TRMS, we design the adaptive controller for angle ISS stabilization to attenuate the influences of uncertain parameters and input disturbances to the angles of TRMS. The robustness of the closed system is shown by the the stabilization of the angles with the yaw and pitch external disturbances, the simulation and experimental results help to proof the rightness of proposed method.